Dental transposition of canine and lateral incisor and impacted central incisor treatment: A case report - Gebert,Tarcisio Jacinto (2014)
INTRODUCTION: Dental transposition and impaction are disorders related to ectopic eruption or failure in tooth eruption, which can affect child physical, mental and social development and may be difficult to be clinically solved. METHODS: We describe a case of transposition between the upper left canine and lateral incisor associated with impaction of the central incisor on the same side, in a 12-year-old patient. Conservative treatment involving surgical-orthodontic correction of transposed teeth and traction of the central incisor was conducted. CONCLUSION: The option of correcting transposition and orthodontic traction by means of the segmented arch technique with devices such as cantilever and TMA rectangular wire loops, although a complex alternative, was proved to be esthetically and functionally effective.